2011
DOI: 10.1042/bj20101717
|View full text |Cite
|
Sign up to set email alerts
|

Novel role for the Lu/BCAM–spectrin interaction in actin cytoskeleton reorganization

Abstract: SynopsisLu/BCAM is a laminin 511/521 receptor, expressed in erythroid and endothelial cells, and in epithelial tissues. The RK573-574 motif of Lu/BCAM cytoplasmic domain interacts with DI-spectrin, the main component of the membrane skeleton in red blood cells. We report that Lu/BCAM binds to the non-erythroid DII-spectrin via the RK573-574 motif. Alanine substitution of this motif abolished the Lu/BCAM-spectrin interaction, enhanced Lu/BCAM half-life at the MDCK cell surface and increased Lu/BCAM-mediated cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…Furthermore, conserved TEAD-binding sites were found in the promoters of Bcam , S1pr2 and Nuak2 (Figure 5C), where the YAP and TEAD proteins reside as revealed by ChIP-Seq and ChIP-qPCR analysis (Figure 5E). BCAM and S1PR2 can activate RhoA (Collec et al, 2011; Randriamboavonjy et al, 2009) to promote pMLC production. The NUAK2 kinase can also enhance pMLC generation by inhibiting MLC phosphatase independently of RhoA (Zagórska et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, conserved TEAD-binding sites were found in the promoters of Bcam , S1pr2 and Nuak2 (Figure 5C), where the YAP and TEAD proteins reside as revealed by ChIP-Seq and ChIP-qPCR analysis (Figure 5E). BCAM and S1PR2 can activate RhoA (Collec et al, 2011; Randriamboavonjy et al, 2009) to promote pMLC production. The NUAK2 kinase can also enhance pMLC generation by inhibiting MLC phosphatase independently of RhoA (Zagórska et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…The Arg 573 Lys 574 motif in the shared cytoplasmic tail of Lu and B-CAM attaches to the spectrin cytoskeleton and regulates cell adhesive activity (32,33). A recent study showed that a Lu/B-CAM-␣II spectrin interaction impacts actin organization in epithelial cells (34). This motif in Lu/B-CAM may be involved in intracellular signaling that mediates cell migration on LM-511.…”
Section: Discussionmentioning
confidence: 99%
“…16,17,29,30 In sickle cell erythrocytes, release of Lu/BCAM from the spectrin network as a consequence of Lu/BCAM phosphorylation is hypothesized to increase Lu/BCAM clustering after ligand binding and therefore enhance erythrocyte adhesion to laminin-a5. 16,30 We wanted to verify whether the mobility of Lu/BCAM within the erythrocyte membrane is impacted by neuraminidase treatment.…”
Section: Loss Of Gpc Binding Does Not Increase Lu/bcam Mobility In Thmentioning
confidence: 99%